Political pluralism in the framework of the post-agreement and in the face of the situation of human rights defenders and social leaders in Colombia - Marín Beltrán, Segundo Eurípides (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The objective of this article is to analyze, from a theoretical and reflective point of view, how the practice of political pluralism can materialize in order to improve the situation of social leaders and human rights defenders in Colombia. The methodology used is based on the consultation of sources that allow us to understand the importance of the notion of pluralism and the role played by defenders of rights. The fact that not only should the existence of rights for legal interpretation be discussed, but also the promotion of these should also be considered. Finally, it is concluded that the Comprehensive Security System for the Exercise of Politics must be strengthened and linked with the different State institutions in order to create a coordinated structure that guarantees the protection of social leaders, their work and the reestablishment of their Rights.